Penyuluhan Rancang Bangun Pembangkit Listrik Menggunakan Alternator Kepada Siswa SMKN 3 Tangerang Selatan - Parlindungan Pandapotan Marpaung (Yayasan Literasi Sains Indonesia, 2024)
Counseling students at SMK Negeri 3 South Tangerang City who have motorbike competency technical skills is very important to understand and understand the function of the alternator from motorbike equipment for generating electrical energy. The source of electrical energy in automotive motorbikes generally comes from a power plant using an alternator (alternating generator) to supply electrical loads, including the electrical load of charging the battery. Implementation of outreach activities is carried out for students in class . The counseling method for class for 90 minutes understand and comprehend in a tutorial the operation of equipment designed to build a power plant using an alternator. The final result is understanding and comprehending the implementation of the counseling given the opportunity to write class comments for 30 minutes on the google classroom page. It was found that 17 students wrote class comments on the results of counseling on the design of power plants using alternators. abstract must be a minimum of 150 words, and a maximum of 300 words, using Indonesian and English in italics with Times New Roman 10. The abstract must be clear, providing a brief overview of the problems and solutions to community service problems. The abstract contains the background or importance of the topic of community service, objectives of community service, service partners; service methods, and a summary of results and conclusions. The abstract ends with comments about the importance of the service results or a short conclusion.